Examination of a Novel Practical Poultry Management Method to Enhance the Effect of Live Eimeria Vaccination for Conventionally Housed Replacement Layer Pullets - Price, K.R.; Guerin, M.T.; Newman, L.; Hargis, B.M.; Barta, J.R. (International Journal of Poultry Science, 2013)
Coccidiosis, an enteric disease caused by Eimeria species, continues to be a substantial economic burden on the global poultry industry. With increased concerns regarding prophylactic antimicrobials to control coccidiosis alternate methods of preventative control have been developed, yet innovation to strengthen these methods has been limited. Live Eimeria vaccination stimulates immunity from the first small dose of vaccinal oocysts and is enhanced through low dose fecal-oral transmission (“cycling”) of these oocysts. This immune response manifests as no pathogenic effects with minimal parasite reproduction. The success of a live coccidiosis vaccine is inextricably linked to poultry management techniques that successfully balance oocyst cycling with modest numbers of infective oocysts. The breadth of cage floor coverage using a durable fibre tray (lasting 5 weeks) to improve oocyst cycling in live vaccinated caged pullets was investigated. Pullets were inoculated via oral gavage with mixed vaccinal Eimeria species and reared under simulated commercial conditions with 0, 20, 40 or 60% tray coverage from hatch to 42 days of age, then subsequently challenged with homologous Eimeria species. Mean total oocyst shed (output) between birds housed with or without coverage differed significantly after challenge infection. Pullets on 40% coverage had significantly lower mean oocyst output than the other treatment groups (>99% compared to no coverage). No difference in mean total oocyst output was found between the 20 and 60% treatment groups. Lesion scores mirrored oocyst shed results. Increased access to oocysts using 40% cage floor coverage with fibre trays over 5 weeks allowed for improved vaccine success in live coccidiosis vaccinated caged pullets.